You need to find the points of intersection between the graphs of `f(theta)` and `g(theta), ` hence, should solve the following equation such that:

`f(theta) = g(theta) => 2 sin theta - 1 = 3 cos theta + 2`

`2 sin theta - 3 costheta = 3`

You should use the following trigonometric identities such that:

`sin theta = (2tan(theta/2))/(1 + tan^2(theta/2))`

`cos theta = (1 - tan^(theta/2))/(1 + tan^2(theta/2))`

Substituting t for `tan(theta/2) ` yields:

`2*(2t)/(1 + t^2) - 3*(1 - t^2)/(1 + t^2) = 3`

You need to bring the terms to a common denominator such that:

`4t - 3 + 3t^2 - 3 - 3t^2 = 0`

Reducing like terms yields:

`4t - 6 = 0 => t = 6/4 => t = 3/2`

You need to solve for x the equation `tan(theta/2) = 3/2 => theta = 2arctan(3/2) + npi` .

**Hence, the equation that has as solutions the points of intersection of graphs is `2 sin theta - 3 cos theta - 3 = 0` and the general solution to this equation is `theta = 2arctan(3/2) + npi.` **